Synthesis and characterization of the Fe3O4@SiO2 nanoparticles - Tessarolli, Barbara Oliveira [UNESP]; Da Silva, Paulo Vitor [UNESP]; Gallardo, Emílio Carlos [UNESP]; Magdalena, Aroldo Geraldo [UNESP] (FapUNIFESP (SciELO), 2019)
In this work the synthesis and characterization of the magnetic nanoparticles of magnetite (Fe3O4) from the methodology via co-precipitation and its subsequent functionalization by silica (SiO2), carried out via sol-gel methodology were studied. The characterization of the nanoparticles was performed by X-ray diffractometry (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR) and zeta potential variation as a function of pH. The results showed that the synthesis of the Fe3O4 and Fe3O4@SiO2 nanoparticles was successful, with a high homogeneity of shape and size, according to the results of the analysis of the images obtained by MET, including the formation of shell structures for the Fe3O4@SiO2 nanoparticles. The functionalization of the magnetite surface was confirmed by the FTIR data and the zeta potential measurements. Surface functionalization by silica causes an increase in nanoparticle size due to the introduction of an inorganic shell around magnetite nanoparticles. The zeta potential curves showed that with the addition of silica, the colloidal stability increases in relation to the magnetite and this increase is related to the functionalized silica that should be minimizing the surface energies around the magnetic nanoparticles.
Síntese e caracterização de nanopartículas de Fe3O4@SiO2
Keywords: Core-shell structure; Functionalization; Magnetite; Silica